Association of plasma lead, cadmium and selenium levels with hearing loss in adults: National Health and Nutrition Examination Survey (NHANES) 2011–2012. Issue 6 (28th September 2022) - Tu, Yaqin; Fan, Guorun; Wu, Nan; Wu, Hao; Xiao, Hongjun
Abstract: To determine the association between hearing loss and environmental Pb, Cd and Se exposure, a total of 1503 American adults from National Health and Nutrition Examination Survey (NHANES) (2011–2012) were assessed. The average of four audiometric frequencies (0·5, 1, 2 and 4 kHz) was used to identify speech-frequency hearing loss (SFHL), while the average of 3 audiometric frequencies (3, 4 and 6 kHz) was used to identify high-frequency hearing loss (HFHL). HFHL adjusted OR determined by comparing the highest and lowest blood Pb and Cd quartiles were 1·98 (95 % CI: 1·27, 3·10) and 1·81 (95 % CI: 1·13, 2·90), respectively. SFHL was significantly associated with blood Cd with the OR = 2·42 for the highest quartile. When further stratified by age, this association appeared to be limited to adults aged 35–52 years. After stratified by gender, except for Pb and Cd, we observed that blood Se showed a dose-dependent association with SFHL in men. In women, only Cd showed a dose-dependent association with speech and high-frequency hearing loss. Hearing loss was positively associated with blood levels of Pb and Cd. Additionally, our study provided novel evidence suggesting that excessive Se supplement would increase SFHL risk in men.